An incremental hash-based optimistic concurrency control scenario for failure management in HDDBs - an application approach. (2015) - Ramesh, Dharavath; Kumar, Chiranjeev; Bitthal, Kumar
During real-time transaction process there is a high probability of transaction failure due to the application of various concurrency control-based protocols and network overload. There are no effective methods to manage these failed transactions that provide the clients an opportunity to renew their transaction in a short span of time. In this paper, we propose a methodology which caters to the need for an effective concurrency control management by providing an efficient way to decrease the real-time as well as non-real-time work done by the server. Our proposed methodology represents an excellent blossom in the failure management environment. This method is based on the calculation of hash value of the data field and compares the current hash value with the previous hash value every time before the write operation takes place. The proposed methodology also allows the client to renew a failed transaction using their previous transaction details. We perform extensive experiments to validate the proposed methodology by using remote method invocation (RMI). By performing extensive experiments, we epitomise the performance of this method with existing modalities. Experimental results show that the proposed methodology can achieve atomicity and optimistic instances for failure transactions in an efficient way.